Issues of Japan Halal Industry: An Exploration of Potential Obstacles to Japanese Smes’ Export Development - Tatsuya Fujiwara; Risyawati binti Mohamed Ismail (International Journal of Supply Chain Management, 2017)
The aims of this paper are to investigate the process of Japanese small and medium-sized enterprises (SMEs) Halal food business toward exporting Halal food and to explore issues of the Japan Halal Industry that potentially interfere SMEs exporting Halal food. In this study, the researcher interviewed three SMEs with Japan Halal certification issued by Japanese Halal certification bodies, two Halal certification bodies recognized by foreign Halal certification bodies, two Halal consultants, two researchers who are familiar with Halal study and three Malaysian Muslim consumers who had visited and/or lived in Japan. By analysing the contents emerged from all the interviews, the findings show the following things. First, the SMEs follow a traditional model of internationalization; they focus on a domestic market first, accumulate experimental knowledge in the domestic market and then, move toward foreign markets. Second, 15 issues categorized into barriers to starting Halal food business, perceptions of Halal food business, Halal certification, consultation of Halal food business and Muslim market in Japan emerged. In light of the traditional model, it is assumed that the issues in Halal certification, consultation of Halal food business and Muslim market in Japan adversely influence SMEs accumulating experimental knowledge of Halal food business. Hence, those issues, possibly become potential obstacles to SMEs export development.